2021
DOI: 10.1097/rlu.0000000000003756
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of 18F-FDG PET/CT in Patients With Aggressive B-Cell Lymphoma Treated With Anti-CD19 Chimeric Antigen Receptor T Cells

Abstract: Purpose of the Report We aimed to evaluate the role of 18F-FDG PET/CT in predicting patient outcome following chimeric antigen receptor T (CAR T) cells infusion in aggressive B-cell lymphoma. Methods 18F-FDG PET/CT data before leukapheresis, before CAR T-cell infusion and 1 month (M1) after CAR T-cell infusion, from 72 patients were retrospectively analyzed. SUVmax, total lesion glycolysis (TLG), metabolic tumor volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 37 publications
5
25
1
Order By: Relevance
“…Therefore, from our results, M1 evaluation seems the preferable slot of time for response assessment in these patients. In addition we have confirmed herein the strong prognostic value of the baseline metabolic tumor volume already reported by us and others 7,23,24 as a tool to identify early progressors. Indeed, the high-risk category with TMTV>80ml at baseline accounted for 70 patients among whom 41% progressed before the M1 evaluation and 11% were in stable or progressive response at M1.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, from our results, M1 evaluation seems the preferable slot of time for response assessment in these patients. In addition we have confirmed herein the strong prognostic value of the baseline metabolic tumor volume already reported by us and others 7,23,24 as a tool to identify early progressors. Indeed, the high-risk category with TMTV>80ml at baseline accounted for 70 patients among whom 41% progressed before the M1 evaluation and 11% were in stable or progressive response at M1.…”
Section: Discussionsupporting
confidence: 88%
“…Baseline high-risk factors, including LDH and ECOG PS, 2,4,5,15 inform patient selection pre–CAR-T, but by the time patients have undergone treatment and have responded, an individual patient’s risk will have changed. On-treatment biomarkers, including imaging markers of response (eg, DS or disease metabolic volume kinetics 16 ), should be incorporated into a dynamic, postinfusion risk model.…”
mentioning
confidence: 99%
“…A lower tumor burden and/or lower tumor FDG uptake have been linked to better outcomes. An early metabolic response after treatment has also proved predictive of therapy success, assessed visually [ 13 , 16 ] or semi-quantitatively using SUV max [ 12 , 13 , 15 ]. In general, the studies performed are however small and mixed results have been reported in terms of which predictive metric to use.…”
Section: Introductionmentioning
confidence: 99%